Sistem Monitoring Konsumsi Beban Listrik Rumah Tangga Realtime Berbasis Website - Ardianto, Feby; Alfaresi, Bengawan; Hendrawan, Muhammad (Fakultas Teknik Universitas Muria Kudus, 2024)
The home automation system, or commonly known as smart home system, is increasingly being utilized due to its ability to provide comfort and convenience to homeowners in monitoring and controlling household appliances remotely and automatically. The implementation of home automation is expected to aid in electricity energy savings. The aim of this research is to monitor household electricity usage in real-time based on a web server. The method used consists of four stages: 1) selection of software and hardware, 2) system design, 3) program development, and 4) testing. The test results of monitoring household electricity usage for three days show that the cost to be paid for electricity consumption after three days of usage with a tariff corresponding to the installed power (1300 VA) is 26,293 Rupiah.